Electromagnetic characterisation of flexible conductive membranes at millimetre‐waves. Issue 5 (1st February 2013) - Romano, P.; Rosset, S.; Maffli, L.; Shea, H.; Perruisseau‐Carrier, J.
Abstract : Presented is the experimental surface impedance characterisation of stretchable conductors at Ka‐band, using a non‐contact technique based on two‐port rectangular waveguide measurements. Two different types of metallisations are analysed, namely gold ion implantation and corrugated Ag deposition on polydimethylsiloxane membranes. The method allows characterising, in a simple configuration, the surface impedance of any thin metallisation, and is able to reduce the effects of tolerances of substrates and the possible gap between the conductive sheet and the holder waveguide. The obtained surface impedances are discussed in the light of potential applications.